Aspectus : développement d’une plateforme collaborative en ligne d’analyse des données 3D pour l’archéologie et le patrimoine - Matthieu Thivet; Quentin Verriez; Damien Vurpillot (In Situ)
The Aspectus project was born out of necessity some years ago, during a post-excavation season. In recent years, we have seen a tenfold increase in the volumes of digital data acquired. This phenomenon of increasing digitisation in the field of archaeology, and of cultural heritage more generally, requires strategies for managing an inordinate quantity of 3D data and making it available to a broad array of researchers and an even broader public audience. Beyond the sheer quantity of data, multimodal and multiresolution data exploitation has become another common challenge. The Aspectus project aims to facilitate access to complex three-dimensional data and to promote collaborative work and remote expert assessment. Aspectus takes advantage of available open-source solutions to produce a comprehensive software solution that encompasses multiple complementary approaches: high quality 3D web visualisation, data analysis and annotation tools, online workplace platform, in other words, making complex 3D data accessible and available for analysis in a collaborative environment. Our first trial concept generated much interest at the Innovative SHS 2017 exhibition and we are now developing a prototype of Aspectus as part of the “Bibracte Numérique” project.